PENGARUH TEKNOLOGI INFORMASI, DESENTRALISASI, KARAKTERISTIK SISTEM AKUNTANSI MANAJEMEN TERHADAP KINERJA MANAJERIAL PADA PT RATU CIPTA MANAGEMENT - Puspita Maelani; Dini Martinda Lestari; Fitiraningsih Fitiraningsih (Journal of Global Business and Management Review, 2021)
Managerial performance that is not well integrated will have implications for things that are not in accordance with the objectives, so it is necessary to improve supporting performance. Therefore, managers must improve work support such as information technology, decentralization, and the characteristics of a good and structured management accounting system in order to produce optimal performance. The purpose of this study was to determine the effect of information technology, decentralization, and characteristics of management accounting systems on managerial performance. The method used in this study is a descriptive method with a quantitative approach through data collection techniques with questionnaires distributed directly to managers and staff at CV. Ratu Cipta Management. The statistical test tool used is SPSS 25. The results of this study were obtained in a t-test (partial) that the first hypothesis of information technology affects managerial performance obtained a t value (Tcount 11.484> Ttable 2.045), the second hypothesis that decentralization has a significant effect on managerial performance is obtained t (T count 3,332 > T table 2,045) and the third hypothesis that the characteristics of the management accounting system have no effect on managerial performance obtained the t value (T count 0,227 < T table 2,045). Simultaneously, the variables of information technology, decentralization and the characteristics of the management accounting system on managerial performance are shown by the Fcount of 12.062 > Ftable 2.92. The results of this study indicate that the variables of information technology and decentralization have an effect on managerial performance, while the characteristics of the management accounting system have no effect on managerial performance, and simultaneously the three variables affect managerial performance.